2018
DOI: 10.5812/aapm.61041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative Administration of Acetaminophen and Melatonin on Retrobulbar Block Associated Pain in Cataract Surgery

Abstract: BackgroundRetrobulbar block is one of the chosen methods for local anesthesia in cataract surgery. Since it is a painful procedure, using analgesic and sedative drugs is recommended. Current medications have side effects and evaluating of new drugs or new uses of existing safer drugs is necessary.ObjectivesThe aim of this study was to compare the administration of melatonin and acetaminophen on pain and hemodynamic changes during retrobulbar block.MethodsIn a double-blinded randomized trial, 180 patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The primary aim of this study was to investigate the effect of Benson's non-pharmacological relaxation therapy on preoperative anxiety and the amounts of propofol consumption for the induction and maintenance of anesthesia during cataract surgery. One of the most surgeries in ophthalmology is cataract surgery (10,11). Based on the obtained results, it can be concluded that Benson's relaxation method effectively reduced preparative anxiety in patients of this study who underwent cataract surgery.…”
Section: Discussionmentioning
confidence: 55%
“…The primary aim of this study was to investigate the effect of Benson's non-pharmacological relaxation therapy on preoperative anxiety and the amounts of propofol consumption for the induction and maintenance of anesthesia during cataract surgery. One of the most surgeries in ophthalmology is cataract surgery (10,11). Based on the obtained results, it can be concluded that Benson's relaxation method effectively reduced preparative anxiety in patients of this study who underwent cataract surgery.…”
Section: Discussionmentioning
confidence: 55%
“…Intraoperative opioid use was reported in 4 studies 18–21 . The meta‐analysis showed a statistically significant reduction of intraoperative opioid consumption (MD −4.14 mg; 95% CI −4.56, −3.73; I 2 = 42%; P < 0.00001) (see Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…Figure 1 shows the flow diagram of the selection of included studies. According to the inclusion and exclusion criteria, 15 studies with a total of 1,102 patients were included in the final analysis 15–21,24–31 . The dosage of melatonin ranged from 1 mg to 10 mg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations